Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a] 4/12 ; 5/12 ; 11/2 ; 1/4
b] 1 ; 9/12; 12/5 ; 11/3
c] 8/21; 6/11;8/7
d] 2/3 ;2/7 15/2
a]1/3 5/12 11/2 1/4
b]1 3/4 12/5 33/9
c]8/21 6/11 8/7
d]2/3 2/7 15/2
A, X x 3/5 + X x 7/5 = 9/4 B, X - 4/7 = 1/5 : 7/2
<=> X x (3/5 + 7/5) = 9/4 <=> X - 4/7 = 2/35
<=> X x 2 = 9/4 <=> X = 2/35 + 4/7 <=> X = 22/35
<=> X= 9/4 : 2 <=> X = 9/8
#HT#
\(a,x.\frac{3}{5}+x.\frac{7}{5}=\frac{9}{4}\)
\(\Leftrightarrow x.\left(\frac{3}{5}+\frac{7}{5}\right)=\frac{9}{4}\)
\(\Leftrightarrow x.2=\frac{9}{4}\)
\(\Leftrightarrow x=\frac{9}{8}\)
\(b,x-\frac{4}{7}=\frac{1}{5}:\frac{7}{2}\)
\(\Leftrightarrow x-\frac{4}{7}=\frac{2}{35}\)
\(\Leftrightarrow x=\frac{22}{35}\)
a)\(\frac{3}{5}+\frac{4}{7}=\frac{21}{35}+\frac{20}{35}=\frac{41}{35}\)
b)\(\frac{2}{3}-\frac{3}{9}=\frac{2}{3}-\frac{1}{3}=\frac{1}{3}\)Hoặc \(\frac{2}{3}-\frac{3}{9}=\frac{6}{9}-\frac{3}{9}=\frac{3}{9}=\frac{1}{3}\)
c)\(\frac{2}{5}\)x\(\frac{8}{11}=\frac{16}{55}\)
d)\(\frac{3}{7}:\frac{6}{14}=\frac{3}{7}\)x\(\frac{14}{6}=\)\(\frac{3x7x2}{7x3x2}\)\(=\)\(1\)
e)\(\frac{3}{8}+\frac{6}{15}:\frac{3}{5}=\frac{3}{8}+\frac{6}{15}\)x\(\frac{5}{3}=\frac{3}{8}+\)\(\frac{2}{3}\)\(=\frac{9}{24}+\frac{16}{24}=\frac{25}{24}\)
Giải cực kì đầy đủ
A \(\frac{3}{5}+\frac{4}{15}=\frac{9}{15}+\frac{4}{15}=\frac{13}{15}\)
B \(\frac{15}{7}-\frac{5}{3}=\frac{45}{21}-\frac{35}{21}=\frac{10}{21}\)
C \(\frac{3}{4}.\frac{5}{7}=\frac{15}{28}\)
D \(\frac{2}{5}\div\frac{7}{3}=\frac{2}{5}\times\frac{3}{7}=\frac{6}{35}\)
a) (36 + 54) x 7 + 7 x 9 + 7=
= 90 x 7 + 7x 9 + 7 x1 =
= 7 x ( 90 + 9 +1) =
= 7 x 100 = 700
b) 5/7 x 3 + 5/7 x 6 + 5/7 =
= 5/7 x (3 + 6 + 1) =
= 5/7 x 10 = 50/7
a) \(\frac{4}{7}:\frac{8}{11}=\frac{4}{7}\times\frac{11}{8}\)
\(=\frac{44}{56}=\frac{22}{23}\)
b) \(\frac{3}{5}+\frac{4}{5}:\frac{2}{5}=\frac{3}{5}+\frac{4}{5}\times\frac{5}{2}\)
\(=\frac{3}{5}+2\)
\(=\frac{13}{5}\)
a: 4/7:8/11=4/7x11/8=44/56=11/14
b: 3/5+4/5:2/5
= 3/5+4/5x5/2
= 3/5+10/5
=13/5
\(\frac{3}{4}x\frac{4}{5}:\frac{3}{5}x\frac{6}{7}:\frac{1}{7}x\frac{5}{6}\)\(=\)\(\frac{3}{4}x\frac{4}{5}x\frac{5}{3}x\frac{6}{7}x\frac{7}{1}x\frac{5}{6}\)\(=\)\(\frac{3x4x5x6x7x5}{4x5x3x7x1x6}\)\(=\)\(\frac{\left(3\right)x\left(4\right)x\left(5\right)x\left(6\right)x\left(7\right)x5}{\left(3\right)x\left(4\right)x\left(5\right)x\left(6\right)x\left(7\right)x1}\)\(=\)\(\frac{5}{1}\)\(=\)\(5\).
a. 870 + 1135 = 2005
b. 691 + 486 - 300 = 877
c. 457 - 236 + 779 = 1000
a) (3480 + 4540) : 4 = 8020 : 4 = 2005
b) ( 3455 + 2430 - 1500) : 5 = 4385 : 5 = 877
c) (3199 - 1652 + 5453 ) : 7 = 7000 : 7 = 1000
Học tốt !!!